Laparoscopic Nephroureterectomy in the Upper Urinary Tract Urothelial Carcinoma with Transvaginal Extraction - Zulfan Hendri, Ahmad; Yuri, Prahara; Zulfiqqar, Andy; Hashfi, Azwar; Soerohardjo, Indrawarman (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The upper urinary tract urothelial carcinoma (UTUC) is a rare urological malignancy. Laparoscopic nephroureterectomy (LNU) is one of the options for minimally invasive surgery for UTUC. It has similar oncological outcomes compared to open nephroureterectomy. One of the techniques developed for specimen extraction is the transvaginal route. Transvaginal specimen extraction has advantages in the reduced risk of complications, faster recovery time, and better end result. CASE PRESENTATION: A 37-year-old woman complained of intermittent pain in her right flank for the past 2 months, with significant weight loss. No other significant symptoms occurred. Her general condition was good with a Karnofsky Performance scale index is 90. In the right periumbilical area, there was a mobile, smooth mass palpated with the size of 10 × 12 cm. There was no tenderness. The patient underwent URS and biopsy of the right ureteral mass with pathological analysis resulting in UTUC. Then, the patient underwent laparoscopic radical nephroureterectomy. CONCLUSION: Although the surgical procedure was safe for the patient and more effective in terms of less morbidity, faster healing time, and better cosmetic appearance, transvaginal extraction of the kidney needs to be further studied, particularly relating to the little experience of this new technique.